2022
DOI: 10.3390/toxics10060338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Inhalation of Electronic Cigarette Vapor Containing Nicotine on Neurobehaviors and Pre/Postsynaptic Neuron Markers

Abstract: Nicotine-exposed animal models exhibit neurobehavioral changes linked to impaired synaptic plasticity. Previous studies highlighted alterations in neurotransmitter levels following nicotine exposure. Vesicular glutamate transporter (VGLUT1) and vesicular gamma-aminobutyric acid (GABA) transporter (VGAT) are essential for the transport and release of glutamate and GABA, respectively, from presynaptic neurons into synapses. In our work, an e-cigarette device was used to deliver vapor containing nicotine to C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It is also critical to discuss that while chloride dyshomeostasis could be the predominant cause of excitatory GABAergic signaling in disorders, reductions in transsynaptic GABAergic signaling should also be considered a potential factor. While the data presented in this review outlined the contributions of downregulated GABA signaling towards stress-induced excitatory GABA A R-mediated responses, reductions in GABAergic signaling are also present in Alzheimer’s disease ( 179 ), ASD ( 100 , 180 ), SUD ( 181 , 182 ). It can be hypothesized that repurposing therapeutics that enhance endogenous levels of GABA could therefore alleviate excitatory GABA A R signaling throughout various disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is also critical to discuss that while chloride dyshomeostasis could be the predominant cause of excitatory GABAergic signaling in disorders, reductions in transsynaptic GABAergic signaling should also be considered a potential factor. While the data presented in this review outlined the contributions of downregulated GABA signaling towards stress-induced excitatory GABA A R-mediated responses, reductions in GABAergic signaling are also present in Alzheimer’s disease ( 179 ), ASD ( 100 , 180 ), SUD ( 181 , 182 ). It can be hypothesized that repurposing therapeutics that enhance endogenous levels of GABA could therefore alleviate excitatory GABA A R signaling throughout various disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The E-liquid vehicle contains 70% Vegetable Glycerin and 30% Propylene Glycol. Nicotine (#N3876, ≥99% [GC], Sigma-Aldrich, Burlington, USA), is added to the vehicle solution to achieve a concentration of 24 mgÁml À1 (Alasmari et al, 2022). A paired Baby V2 S2 0.15 Ohm coil is used to create clouds of vape smoke.…”
Section: Vapour Exposure Chamber Modelmentioning
confidence: 99%
“…Both Zebrafish and human studies have reported neurobehavioral effects following e-cigarette exposure. Zebrafish exposed to e-cigarette aerosols altered locomotor activity and anxiety-like behaviors [ 59 , 126 , 132 , 133 , 134 , 135 ], similar to human behavioral changes [ 136 , 137 ].…”
Section: Comparison Of E-cigarette Impacts: Zebrafish Vs Human Studiesmentioning
confidence: 99%